Hand Washing with Soap: The Most Effective ‘Do-It-Yourself’ Vaccine? - Hiremath , Ravishekhar N; Kotwal , Atul; Kunte , Renuka; Hiremath , Sandhya V; Venkatesh (National Journal of Community Medicine, 2012)
Hand washing is one of the most effective means of preventing diseases and have a major impact on public health in any country. It is known to significantly reduce the two leading causes of mortality – diarrheal diseases and acute respiratory infections, including the recent outbreak of pandemic influenza. Because hand washing with soap can prevent the transmission of a variety of pathogens, it may be more effective than any single vaccine or hygiene behaviour. Promoted broadly enough, hand washing with soap can be viewed as an essential do-it-yourself vaccine. “Good hand hygiene is the first line of defense against spread of many illnesses”. Therefore public should be provided with adequate knowledge and tools to enable them to protect themselves and their families from infection and illness by practicing proper hand hygiene through support of key stakeholders, Government, industry, and donors who can offer unique resources which are necessary to ensure the success of a large-scale program. Conducting a situation assessment and, where needed, making the case for hand washing on topics ranging from cost effectiveness to health impact will give the hand washing program a solid foundation. This is the important time to re-look at our hand hygiene habits, for hands are the key carrier of germs that spread infections, and good hand hygiene is the one tool within easy reach of everyone, that can reduce the risk of infection. If the millennium development targets for reduction in child mortality are to be met, hand washing habits must be improved.